2007
DOI: 10.1111/j.1540-4781.2007.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Students' and Teachers' Assessments of the Need for Accuracy in the Oral Production of German as a Foreign Language

Abstract: Previous research indicates that foreign language learners are much more focused on accuracy, particularly grammatical accuracy, than their teachers are. The purpose of the current study was to gain a more detailed understanding of American learners' views of the need for accuracy in the oral production of a foreign language (German) by (a) distinguishing among 4 different purposes of language use (deriving a personal sense of accomplishment; being comprehensible to a native speaker [NS]; being pleasant to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 79 publications
2
11
0
Order By: Relevance
“…These may include motivation, anxiety, self-regulation, learner autonomy, gender, language proficiency, and strategy use (e.g., Cotterall, 1999;Horwitz, 1990;Peacock, 1999;Siebert, 2003;Tanaka & Ellis, 2003;Wenden, 1991Wenden, , 1999Yang, 1999). There is also evidence that certain beliefs are common among learners, teachers, target languages, cultures, instructional settings, and age groups (e.g., Chavez, 2007;Horwitz, 1999;Peacock, 2001;Schulz, 1996Schulz, , 2001. Today, however, learner beliefs are no longer seen as "stable mental representations that are fixed a priori constructs" (Kalaja & Barcelos, 2003, p. 2) but rather as highly dynamic because they can change in light of one's situation, emotional state, and company (Barcelos & Kalaja, 2011).…”
mentioning
confidence: 99%
“…These may include motivation, anxiety, self-regulation, learner autonomy, gender, language proficiency, and strategy use (e.g., Cotterall, 1999;Horwitz, 1990;Peacock, 1999;Siebert, 2003;Tanaka & Ellis, 2003;Wenden, 1991Wenden, , 1999Yang, 1999). There is also evidence that certain beliefs are common among learners, teachers, target languages, cultures, instructional settings, and age groups (e.g., Chavez, 2007;Horwitz, 1999;Peacock, 2001;Schulz, 1996Schulz, , 2001. Today, however, learner beliefs are no longer seen as "stable mental representations that are fixed a priori constructs" (Kalaja & Barcelos, 2003, p. 2) but rather as highly dynamic because they can change in light of one's situation, emotional state, and company (Barcelos & Kalaja, 2011).…”
mentioning
confidence: 99%
“…Three‐hundred‐and‐forty‐nine students of German enrolled in first‐ (N = 105), second‐ (N = 170), and third‐ (N = 74) year courses at a large Midwestern university in the US participated in this study. Previous statistical analyses (Chavez ) showed that students in the first three years of the German program responded without significant differences to the questionnaire items that constituted the research instrument. Therefore, in the analyses applied in the current study, students in years 1, 2, and 3 of instruction were treated as one population.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, the paper's aims are to highlight the complex interaction between learner variables and beliefs about accuracy and to underscore that evidence of (in)accuracy should be considered not just in light of cognitive but also social‐attitudinal influences. The study reported on here relates to an earlier one (Chavez ) that used the same data set but examined the study population taken as a whole, i.e. without regard to learner variables.…”
Section: Focus and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Students, of course, also have preconceived views on demands for accuracy depending on, among other things, the specific language to be learned, contexts of language use and beliefs about factors affecting setting of grades (see Chavez 2007). Sometimes students actually wish for more emphasis on formal correctness than teachers do (see Brown 2009;Ellis 2004;Horwitz 1988;Schulz 2001;Sharwood Smith 1988).…”
Section: The Role Of Grammar In Language Teaching and Learningmentioning
confidence: 99%